High speed and high resolution demodulation system for hybrid WDM/FDM based fiber microstructure sensor network by using Fabry-Perot filter - Cheng, Jianwei; Sun, Q.; Ai, F.; Li, X.; Liu, D.; Zhang, L. (2015)
© 2015 OSA. Hybrid WDM/TDM enabled microstructure based optical fiber sensor network with large capacity is proposed. Assisted by Fabry-Perot filter, the demodulation system with high speed of 500Hz and high wavelength resolution less than 4.91pm is realized.